Boron Doped Graphene 3-Dimensi untuk Superkapasitor Kapasitas Tinggi - Sari, Nurlia Pramita; Sonief, Achmad As'ad; Ching, Yuan Su (Rekayasa Mesin, 2017)
Chemical doping is an effective approach to improve the property of carbon material. In this study boron doped graphene with 3D structure used as the electrode was investigated. Boron doped graphene was prepared through freeze-dried process followed by pyrolysis of graphene oxide (GO) with three types of chemical substances; boron oxide, boric acid, and boron powder in an argon and hydrogen atmosphere at 1000 C for 3 hours. The difference of chemical composition generated a different percentage of boron bond with GO. The results shows that the highest electrochemical performance was found in graphene samples with the addition of boric acid (BA) 86 F/g, followed by boron oxide (BO) 59.2 F/g, and boron powder (BP) 2 F/g. It can be caused by boron concentration bound with graphene. The higher concentration of boron could be increased the electrochemical performance due to better of ion movement.